S-Nitrosylation Positively Regulates Ascorbate Peroxidase Activity during Plant Stress Responses. Issue 4 (9th February 2015) - Yang, Huanjie; Mu, Jinye; Chen, Lichao; Feng, Jian; Hu, Jiliang; Li, Lei; Zhou, Jian-Min; Zuo, Jianru
Abstract : Nitric oxide positively regulates a key Arabidopsis peroxidase through S-nitrosylation and enhances resistance to oxidative stresses. Abstract: Nitric oxide (NO ) and reactive oxygen species (ROS ) are two classes of key signaling molecules involved in various developmental processes and stress responses in plants. The burst of NO and ROS triggered by various stimuli activates downstream signaling pathways to cope with abiotic and biotic stresses. Emerging evidence suggests that the interplay of NO and ROS plays a critical role in regulating stress responses. However, the underpinning molecular mechanism remains poorly understood. Here, we show that NO positively regulates the activity of the Arabidopsis ( Arabidopsis thaliana ) cytosolic ascorbate peroxidase1 (APX1). We found that S -nitrosylation of APX1 at cysteine (Cys)-32 enhances its enzymatic activity of scavenging hydrogen peroxide, leading to the increased resistance to oxidative stress, whereas a substitution mutation at Cys-32 causes the reduction of ascorbate peroxidase activity and abolishes its responsiveness to the NO -enhanced enzymatic activity. Moreover, S -nitrosylation of APX1 at Cys-32 also plays an important role in regulating immune responses. These findings illustrate a unique mechanism by which NO regulates hydrogen peroxide homeostasis in plants, thereby establishing a molecular link between NO and ROS signaling pathways.